İstanbul'dan Medine'ye bir tarih belgeseli : Hicaz demiryolu = From İstanbul to Madinah, A documentary of history The Hejaz Railway - Aksay, Mustafa (İstanbul Albaraka Türk, 1999)
İçindekiler
Türkçe-İngilizce
Keywords: Hejaz Railway _ History Railroads _ Saudi Arabia _ History Hejaz (Saudi Arabia) _ History Turkey _ Foreign economic relations _ Saudi Arabia Saudi Arabia _ Foreign economic relations _ Turkey Turkey _ Pictural works Hicaz Demiryolu _ Suudi Arabistan _ Tar